The Influence of Learning Motivation and Intellectual Intelligence on Learning Achievement in Islamic Religious Education - Desti Widiani; Lilik Istiqomah (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2021)
This study aims to examine the influence of learning motivation and intellectual intelligence on students’ learning achievement in PAI (Pendidikan Agama Islam/ Islamic Religious Education). This study applied a quantitative approach using survey technique. The population of this study was students of class VIII MTs (Madrasah Tsanawaiyah/ Islamic Junior High School) Muhammadiyah Gemolong and the sample was determined randomly. The data were analysed using descriptive statistical methods, validity tests, reliability tests, and multiple regression analysis. The results show that there was a significant effect of both intellectual intelligence and learning motivation on student’ learning achievement in PAI with Fcount 10.013 > Ftable 0.000; significance value 2 and 2.66 with α = 0.05 and 0.01.